Abuse of Religious Authority: A Case Study of Walid’s Sexual Violence in the Bidaah Series from the Perspective of Q.S. Al-Mu’minun: 5 - Ulin Nuha Fauziati; Ahmad Saerozi (SENTRI: Jurnal Riset Ilmiah, 2026)
This study investigates the abuse of religious authority in the representation of sexual violence committed by the character Walid in the Malaysian drama series Bidaah, using the ethical principle of safeguarding honor (ḥifẓ al-furūj) in Q.S. Al-Mu’minun: 5 as an interpretive lens. The topic is significant because authority in religious settings can function as moral guidance yet may also be instrumentalized to legitimize domination, silence victims, and normalize abuse. Employing a qualitative design, this research combines netnography and library research. Netnography is used to examine the series’ narrative structure, dialogue, and surrounding digital discourse, while library research analyzes classical and contemporary Qur’anic exegesis as well as scholarship on power relations and authority-based sexual violence. The findings show that Walid’s abuse operates through (1) the manipulation of sexual consent framed as religious obedience, (2) coercion of intimacy via spiritual threats and moral guilt, (3) disciplinary control over victims’ bodies and social relations, and (4) repetitive and systematic sexual exploitation within a closed religious community. These practices demonstrate how “truth” claims and sacred symbolism can function as mechanisms of power that erode bodily autonomy and the capacity to refuse. Furthermore, this research enriches understanding of how “silencing” of victims operates in closed religious communities, making resistance and access to justice highly constrained. From the perspective of Q.S. Al-Mu’minun: 5, both classical and contemporary interpretations emphasize that such acts violate faith-based ethics, human dignity, and the moral objectives of Islam. This study concludes that sexual violence grounded in religious authority has no theological legitimacy and constitutes a severe deviation in religious practice.